Inventory Control Processing System (ICProS) - Zulkarnain Hussein, Afiq Faiz; Abdul Ghani, Farizawani; Mohamed, Hasiah; Nor Adzmi, Nurul Husna Amalina (SOTVI, 2019)
Â Nowadays, many companies use modern technology in the operationof their business. However, there are some companies that still use thetraditional way in processing their data and one of this is OrganizationA. The business process in Organization A is still using manual wayon monitoring daily transactions and managing an inventory. All thenecessary records of completed transaction are being filled in differentways such as log book, papers of letters and forms. Observation andinterviewed with the staf in charge has been conducted and there is aneed for Organization A to have a computerization system to lessentheir work: procedures and process flow; and can secure files andinformation within their business as the data will be save into thedatabase. An online system known as Inventory Control ProcessingSystem (ICProS) is developed to assist in establishing the monitoringprocess of the inventory in Organization A. Adapted Waterfall Modelhas been used in the system development process that consists of 5phases; planning, analysis, system design, system development andtesting. Evaluation has been conducted for 30 respondents and resultshows that respondents perceive ICProS as a useful system that can beimplemented in Organization A (Mean=3.99, SD=0.755). Result ofthe evaluation also indicate that there are some improvement needed(interface and feedback) before the system can be implemented.